2020
DOI: 10.21203/rs.3.rs-21976/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lifetime co-occurring psychiatric disorders in newly diagnosed adults with Attention Deficit Hyperactivity Disorder (ADHD) or/and Autism Spectrum Disorder (ASD)

Abstract: Background: Co-occurring psychiatric disorders in adults with Attention Deficit Hyperactivity Disorder (ADHD) and/or Autism Spectrum Disorder (ASD) contribute to the burden of the healthcare and possibly to the delay of diagnosis. Aim of the study was to clinically assess the prevalence and compare lifetime co-occurring psychopathology in a sample of newly diagnosed ADHD and/or ASD adults and discuss the diagnostic challenges they pose.Methods: The lifetime prevalence rates of ten of the most frequently co-occ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…47 However, another two studies did not find a significant difference in the risk of psychotic disorders between the ASD + ADHD group and the ASDalone group. 46,48 Family history of schizophrenia or ASD The current study found that patients with ASD having a family history of schizophrenia were prone to developing schizophrenia, whereas those with a family history of ASD were not. This finding supports the multiple overlapping etiology model, which tried to explain the co-occurrence of ASD and schizophrenia.…”
Section: Protective Factors Sexmentioning
confidence: 58%
See 2 more Smart Citations
“…47 However, another two studies did not find a significant difference in the risk of psychotic disorders between the ASD + ADHD group and the ASDalone group. 46,48 Family history of schizophrenia or ASD The current study found that patients with ASD having a family history of schizophrenia were prone to developing schizophrenia, whereas those with a family history of ASD were not. This finding supports the multiple overlapping etiology model, which tried to explain the co-occurrence of ASD and schizophrenia.…”
Section: Protective Factors Sexmentioning
confidence: 58%
“…Although ASD, ADHD, and schizophrenia share genetic susceptibility, the present study found that comorbid ADHD in patients with ASD was associated with a decreased risk of schizophrenia 39 . Research data on the co‐occurrence of schizophrenia and ASD with/without ADHD are still scarce 46 . A Norwegian population study reported that the ASD + ADHD group had higher risk of schizophrenia spectrum disorder than the ASD‐alone group 47 .…”
Section: Protective Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was part of a larger research project on de novo diagnosed adults with ADHD and ASD (Pehlivanidis et al, 2020). The multi-disciplinary team that carries out all assessments consists of: psychiatrists who have extended experience in the diagnosis and treatment of Neurodevelopmental Disorders in adults and are trained in ADOS (Lord et al, 2012;Papanikolaou et al, 2009), ADI-R (Le Couteur et al, 2003;Papanikolaou et al, 2009) and DIVA (Kooij et al, 2019a;2019b); and clinical psychologists.…”
Section: Participantsmentioning
confidence: 99%
“…ADHD is commonly comorbid with depression. According to Pehlivanidis, psychiatric disorders, especially depressive disorders, are highly prevalent comorbidities of newly diagnosed adult ADHD [15]. The prevalence of depression in ADHD ranges from 18.6 to 53.3% [1,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%